Controlled Pulmonary Drug Delivery - Smyth, Hugh D.C; Hickey, Anthony J. (Advances in Delivery Science and Technology, 2011)
This distinctive text provides a toolbox for pharmaceutical scientists and those involved in product development utilizing pulmonary drug delivery systems. Uniquely focusing on aspects of control, both temporal and spatial, the text collects a broad range of interlinked chapters that provide both theoretical and practical insight.   Controlled Pulmonary Drug Delivery begins by examination of the foundations for pulmonary drug delivery: the macro and microstructure of the airways, lung clearance, airway absorption and transport, aerosol physics, and a historical overview of the field. Unlike other texts, these chapters are written specifically with drug delivery in mind. The science and technology of inhaler devices, technologies, materials, and particles systems are covered. Testing methods and techniques are discussed before regulatory perspectives and performance specifications conclude the text. The twenty two novel chapters in this volume each provide a theoretical and practical set of tools that comprise a comprehensive toolbox.   This volume will be of interest to scientists and engineers developing pulmonary drug delivery systems. The unique themes of controlled release science and technology that run through the book ensure that experienced and newcomers will greatly benefit from this book. As the importance for control over therapeutic performance is better recognized and demanded, this text will be essential for those delivering bioactives to the lung. Dr. Hugh Smyth is Assistant Professor of Pharmaceutics at the University of Texas, Austin. He is a recipient of the Young Investigator in Pharmaceutics and Pharmaceutical Technology Award of the American Association of Pharmaceutical Scientists and has edited a volume on pulmonary drug delivery. Drs. Hickey and Smyth share a research interest in the delivery of drugs to the lungs for the treatment and prevention of a number of diseases. Dr. Anthony Hickey is Professor of Molecular Pharmaceutics and Biomedical Engineering at the University of North Carolina at Chapel Hill. He is a fellow of the Institute of Biology, American Association of Pharmaceutical Scientists and the American Association for the Advancement of Science. He has published several edited and authored volumes in the fields of pharmaceutical aerosols, process engineering and particulate science.